Gender convergence in the labor market - Polachek, S. W.; Tatsiramos, Konstantinos; Zimmermann, Klaus F. (Emerald, 2015)
For most countries, womens labor force participation and hours of work has risen while mens have fallen. Concomitantly, mens and womens wages and occupational structures have been converging. This volume contains new and innovative research on issues related to gender convergence in the labor market. Topics include patterns in lifetime work, earnings and human capital investment, the gender wage gap, gender complementarities, career progression, the gender composition of top management, and the role of parental leave policies. Among the questions answered are: Do the levels of and returns to human capital change over the last 50 years in the US? Can the shorter fecundity horizon for females (a biological constraint) explain the division of labor in the home and the resulting wage gap? Does skill-biased technological change favor womens wages more than mens? Do care sector jobs incur a wage penalty? What impact does this have on firm and employee outcomes? Does the glass-ceiling faced by women in top management relate to fertility and parental leave policies and having children? And finally, are men and women complements or substitutes in the labor market?
Keywords: Labor market -- Sex differences.; elektronické knihy; electronic books